Low Zika virus seroprevalence in Vientiane, Laos, 2003-2015 - Pastorino, B; Sengvilaipaseuth, O; Chanthongthip, A; Vongsouvath, M; Souksakhone, C; Mayxay, M; Thirion, L; Newton, P; De Lamballerie, X; Dubot-Pérès, A (American Society of Tropical Medicine and Hygiene, 2019)
Zika virus (ZIKV) has been presumed to be endemic in Southeast Asia (SEA), with a low rate of human infections. Although the first ZIKV evidence was obtained in the 1950s through serosurveys, the first laboratory-confirmed case was only detected in 2010 in Cambodia. The epidemiology of ZIKV in SEA remains uncertain because of the scarcity of available data. From 2016, subsequent to the large outbreaks in the Pacific and Latin America, several Asian countries started reporting increasing numbers of confirmed ZIKV patients, but no global epidemiological assessment is available to date. Here, with the aim of providing information on ZIKV circulation and population immunity, we conducted a seroprevalence study among blood donors in Vientiane, Laos. Sera from 359 asymptomatic consenting adult donors in 2003-2004 and 687 in 2015 were screened for anti-ZIKV IgG using NS1 ELISA assay (Euroimmun, Germany). Positive and equivocal samples were confirmed for anti-ZIKV-neutralizing antibodies by virus neutralization tests. Our findings suggest that ZIKV has been circulating in Vientiane over at least the last decade. Zika virus seroprevalence observed in the studied blood donors was low, 4.5% in 2003-2004 with an increase in 2015 to 9.9% (P = 0.002), possibly reflecting the increase of ZIKV incident cases reported over this period. We did not observe any significant difference in seroprevalence according to gender. With a low herd immunity in the Vientiane population, ZIKV represents a risk for future large-scale outbreaks. Implementation of a nationwide ZIKV surveillance network and epidemiological studies throughout the country is needed.